How are nitrogen availability, fine‐root mass, and nitrogen uptake related empirically? Implications for models and theory. (6th January 2019) - Dybzinski, Ray; Kelvakis, Angelo; McCabe, John; Panock, Samantha; Anuchitlertchon, Kanyarak; Vasarhelyi, Leah; McCormack, M. Luke; McNickle, Gordon G.; Poorter, Hendrik; Trinder, Clare; Farrior, Caroline E.
Abstract: Understanding the effects of global change in terrestrial communities requires an understanding of how limiting resources interact with plant traits to affect productivity. Here, we focus on nitrogen and ask whether plant community nitrogen uptake rate is determined (a) by nitrogen availability alone or (b) by the product of nitrogen availability and fine‐root mass. Surprisingly, this is not empirically resolved. We performed controlled microcosm experiments and reanalyzed published pot experiments and field data to determine the relationship between community‐level nitrogen uptake rate, nitrogen availability, and fine‐root mass for 46 unique combinations of species, nitrogen levels, and growing conditions. We found that plant community nitrogen uptake rate was unaffected by fine‐root mass in 63% of cases and saturated with fine‐root mass in 29% of cases (92% in total). In contrast, plant community nitrogen uptake rate was clearly affected by nitrogen availability. The results support the idea that although plants may over‐proliferate fine roots for individual‐level competition, it comes without an increase in community‐level nitrogen uptake. The results have implications for the mechanisms included in coupled carbon‐nitrogen terrestrial biosphere models (CN‐TBMs) and are consistent with CN‐TBMs that operate above the individual scale and omit fine‐root mass in equations of nitrogen uptake rate but inconsistent with the majority of CN‐TBMs, which operate above the individual scale and include fine‐root mass in equations of nitrogen uptake rate. For the much smaller number of CN‐TBMs that explicitly model individual‐based belowground competition for nitrogen, the results suggest that the relative (not absolute) fine‐root mass of competing individuals should be included in the equations that determine individual‐level nitrogen uptake rates. By providing empirical data to support the assumptions used in CN‐TBMs, we put their global climate change predictions on firmer ground. Abstract : We performed controlled microcosm experiments and reanalyzed published pot experiments and field data to determine the relationship between community‐level nitrogen uptake rate, nitrogen availability, and fine‐root mass for 46 unique combinations of species, nitrogen levels, and growing conditions. Plant community nitrogen uptake rate was unaffected by fine‐root mass in 63% of cases and saturated with fine‐root mass in 29% of cases. In contrast, plant community nitrogen uptake rate was clearly affected by nitrogen availability. The results support the idea that although plants may over‐proliferate fine roots for individual‐level competition, it comes without an increase in community‐level nitrogen uptake.